Distortionary Company Car Taxation: Deadweight Losses through Increased Car Ownership - Jos N. van Ommeren; Eva Gutierrez-i-Puigarnau (Tinbergen Institute, 2011)
We analyse the effects of distortionary company car taxation through increased household carownership for the Netherlands. We use several identification strategies and demonstrate thatfor about 20 percent of households company car possession increases car ownership. Theannual welfare loss of distortionary company taxation through increased car ownership isgenerally rather small, maximally exteuro120 per company car, and likely much less. However, forpolicies that exempt households from paying tax on their company car, the annual deadweightloss is likely higher.
urn:NBN:nl:ui:31-1871/38536
Keywords: D12; D61; J33; R41; R48; 330; Fringe benefits; taxation; company car; Fuhrpark; Kraftfahrzeugsteuer; Steuerreform; Steuerwirkung; Privater Haushalt; Niederlande